DRAMATURGI PRESENTASI DIRI DAN OTORITAS DAKWAH DIGITAL DI JAWA BARAT;: Living Qur’an dan Hadis di Status WhatsApp Tokoh Mathla’ul Anwar Pandeglang-Banten, Jawa Barat - Asep Iwan Setiawan; Rohmanur Aziz; Hery Saparudin; Ridwan Rustandi (STAIN Majene, 2026)
This article analyses WhatsApp Status as an arena for the living Qur’an and living hadith, and as a medium of digital da’wah among figures of Mathla’ul Anwar in West Java and Banten. Using a qualitative approach that combined the living Qur’an, living hadith, and Goffman’s dramaturgical theory, data were collected through non-participant observation, in-depth interviews with 15 informants, and documentation from January to March 2026. Four patterns of scriptural reception are identified: textual-normative, reflective-contextual, documentary-performative, and identity-organizational. WhatsApp Status functions as a semi-private da’wah stage where Qur’anic verses, hadith fragments, and organizational symbols are managed through deliberate self-presentation strategies. Digital da’wah authority is built through consistency, trust, and relational closeness within jamaah networks rather than virality. This study extends the living Qur’an and living hadith framework into digital semi-private spaces, demonstrating that scriptural reception is simultaneously performative, relational, and organizational.